Peran Orang Tua dalam Pencegahan Stunting pada Anak Usia Dini di Desa Wawowae - Bonifasia Dhua; Elisabeth Tantiana Ngura; Efrida Ita; Andi Nafsia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the role of parents in preventing stunting in early childhood as a critical growth period in Wawowae Village. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, environmental observations, and documentation of nutritional status at the Posyandu. Data analysis was conducted using the Miles, Huberman, and Saldana model, which includes data reduction, data display, and conclusion drawing. The results showed that low parental nutritional literacy impacts the lack of awareness in monitoring child growth. Feeding practices are still dominated by low-animal protein menus, exacerbated by limited family economic access to nutritious food. Although health facilities are available, the implementation of nutritional parenting and Clean and Healthy Living Behavior (PHBS) at the household level is inconsistent. This study concludes that stunting prevention requires synergy between increasing nutritional literacy, active family involvement, and intensive assistance from health workers to create sustainable interventions.